CUSTOMER RELATIONSHIP MANAGEMENT: UPAYA PENCAPAIAN PROFITABILITAS JANGKA PANJANG - Triastity, Rahayu (Universitas Slamet Riyadi, 2010)
ABSTRACT The rapidly and constantly changing business environment has forced businesses to reconsider their strategies in maintaining their customer base. Customers nowadays have a wide array of product choices, and worst â€“ they are becoming increasingly disloyal. Such facts pose serious threats for some companies. For those who want to keep their customer base, an integrated approach of maintaining and managing customer relationship must be taken. This article proposes an integrated framework of managing relationship with customers. Database marketing, total quality philosophy, value chain integration, customer service-oriented culture, and strategic human resource management must be implemented comprehensively to provide customer satisfaction and long-term beneficial relationship which eventually will increase profitability. Â Keywords: customer relationship management, relationship marketing, total quality, database marketing customer satisfaction, long-term relationship, value chain integration, profitabilitas.